Aged refuse enhances anaerobic fermentation of food waste to produce short-chain fatty acids. (October 2019) - Zhao, Jianwei; Jing, Yiming; Zhang, Jing; Sun, Yingjie; Wang, Yanan; Wang, Huawei; Bi, Xuejun
Graphical abstract: Highlights: AR promoted anaerobic fermentation of food waste to produce SCFA. AR accelerated the disintegration of food waste to release soluble organic matter. AR improved the degradation of two major proteins in food waste simultaneously. Abstract: In this work, a new technology of intensifying anaerobic fermentation of food waste to accumulate SCFA by using landfill degradation product aged refuse (AR) was reported. The experimental results showed that AR enhanced the accumulation of SCFA, and when the optimal dosage of AR was 300 mg/g, the maximum accumulation of SCFA was 32.5 g/L, which was around 1.9 times that of the blank group. Mechanism investigations had shown that AR accelerated the disintegration of food waste to release soluble carbohydrates and proteins. The model experiment of synthetic wastewater revealed that AR improved both hydrolysis and acidification efficiencies but inhibited the methanogenesis process, thereby accumulating SCFA. 454 high-throughput sequencing showed that AR increased the relative abundance of Clostridium and Sporanaerobacte r, which benefited anaerobic hydrolysis of food waste.